Certain Associations Between Iron Biomarkers and Total and γ' Fibrinogen and Plasma Clot Properties Are Mediated by Fibrinogen Genotypes - Rautenbach, Petro H.; Nienaber-Rousseau, Cornelie; de Lange-Loots, Zelda; Pieters, Marlien (Frontiers in Nutrition, 2021)
Introduction: Evidence for the relationship between body iron and cardiovascular disease is inconsistent and mechanisms remain poorly understood. Therefore, we investigated whether iron status is associated with hemostatic factors such as total and γ’ fibrinogen as well as the ensuing plasma fibrin clot properties, and determined whether there are interactions with iron biomarkers and fibrinogen and FXIII single nucleotide polymorphisms (SNPs) in relation to fibrinogen concentration and functionality. Methods: This cross-sectional analysis of 2,010 apparently healthy Black South Africans was part of the South African arm of the Prospective Urban and Rural Epidemiology (PURE) study. Results: Total but not %γ’ fibrinogen negatively correlated with serum iron concentrations, although both decreased over iron tertiles. %γ’ fibrinogen correlated negatively with transferrin and decreased over the transferrin tertiles. A weak negative association between total fibrinogen and transferrin saturation (TSAT) was detected with fibrinogen decreasing over the TSAT tertiles and categories based on TSAT. Lag time correlated positively with transferrin and increased over transferrin tertiles when adjusting for fibrinogen. Before adjusting for fibrinogen lag time were lower in those with adequate iron status based on TSAT. Clot lysis time (CLT) negatively correlated with ferritin and was longer in the first than the third ferritin tertile. Among iron status categories based on ferritin, only CLT differed and was longer in those with adequate iron than iron-overload. CLT negatively correlated with TSAT albeit weakly, shortened over the TSAT tertiles and was faster in those with adequate iron based on TSAT categories. Interactions were observed between FGB SNPs and some of the markers of iron status investigated, in relation to the clot properties. Iron modulated the influence of the SNPs so that for the majority iron was beneficial in respect of clot properties, but even more so for a minority group harboring specific variant alleles. Conclusion: This is the first large-scale epidemiological study to relate fibrinogen concentration and functionality to markers of iron status and to take genetic factors into consideration. We show relationships between key markers of hemostasis and markers of iron status. Iron biomarkers furthermore modulate the influence of fibrinogen SNPs on clot properties.